2004
DOI: 10.1063/1.1815341
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and particle adsorption in nanoflows

Abstract: Molecular dynamics simulations are used to study the behavior of closely-fitting spherical and ellipsoidal particles moving through a fluid-filled cylinder at nanometer scales. The particle, the cylinder wall and the fluid solvent are all treated as atomic systems, and special attention is given to the effects of varying the wetting properties of the fluid. Although the modification of the solid-fluid interaction leads to significant changes in the microstructure of the fluid, its transport properties are foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31] The topology of the time-averaged velocity field has received much attention because it is similar to the s 2 t 2 flow considered in a sphere by Dudley and James. 32 This topology generates a stationary kinematic dynamo [33][34][35] whose main component is a dipole perpendicular to the rotation axis ͑an "m = 1" mode in cylindrical coordinates͒. The threshold, in magnetic Reynolds number, for kinematic dynamo generation is very sensitive to details of the mean flow such as the poloidal to toroidal velocity ratio, [33][34][35] the electrical boundary conditions, [34][35][36][37][38] or the details of the velocity profile near the impellers.…”
Section: B the Vks Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31] The topology of the time-averaged velocity field has received much attention because it is similar to the s 2 t 2 flow considered in a sphere by Dudley and James. 32 This topology generates a stationary kinematic dynamo [33][34][35] whose main component is a dipole perpendicular to the rotation axis ͑an "m = 1" mode in cylindrical coordinates͒. The threshold, in magnetic Reynolds number, for kinematic dynamo generation is very sensitive to details of the mean flow such as the poloidal to toroidal velocity ratio, [33][34][35] the electrical boundary conditions, [34][35][36][37][38] or the details of the velocity profile near the impellers.…”
Section: B the Vks Experimentsmentioning
confidence: 99%
“…32 This topology generates a stationary kinematic dynamo [33][34][35] whose main component is a dipole perpendicular to the rotation axis ͑an "m = 1" mode in cylindrical coordinates͒. The threshold, in magnetic Reynolds number, for kinematic dynamo generation is very sensitive to details of the mean flow such as the poloidal to toroidal velocity ratio, [33][34][35] the electrical boundary conditions, [34][35][36][37][38] or the details of the velocity profile near the impellers. 38 Specific choices in the actual flow configuration have been based on a careful optimization of the kinematic dynamo capacity of the VKS mean flow.…”
Section: B the Vks Experimentsmentioning
confidence: 99%
“…In general, it was shown that the slip length is a tensor quantity for flows over anisotropic textured surfaces [9][10][11][12]. Transport properties of chemically homogeneous nanoparticles were recently studied in cylindrical pores filled with a wetting fluid [13] and in an atomistic solvent confined between flat walls [14]. However, the diffusion process of individual Janus particles even in the absence of flow or confinement remains not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in previous work, MD simulations have provided valuable insight into the transport of suspended solid particles under geometric confinement at nanometer scales. [12][13][14] In the present work, our attention is focused on the effect that fluid density has on the mobility of nanometer particles in nanochannels. Specifically, we examine the mobility of a Lennard-Jones type nanoparticle, moving under the action of a uniform external force, inside a platinum nanochannel filled with nitrogen fluid molecules.…”
Section: Introductionmentioning
confidence: 99%